2017
DOI: 10.1155/2017/5057941
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Adults with Anterior Mandibular Teeth Crowding: Reliability of Little’s Irregularity Index

Abstract: The attempt of this article was to assess reliability of Little's Irregularity Index (LII) as for stability of the treatment outcomes in adults with crowded mandibular incisors. LII was measured on a digital cast prior to an orthodontic treatment (T1) of the 302 patients thus allowing us to establish the treatment plan, which called for (a) expansion (group 1), interproximal stripping (group 2), or extraction of one of the mandibular incisors. LII was measured after debonding (T2) and a year after retention (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…After molding the relevant jaw and preparing the cast, the following items were examined: (7) Determining the distal movement of the canine tooth independent of other anterior teeth towards the space obtained from the extraction of the first deciduous molars by comparing the distance between the mesial surface of lateral teeth to the distal surface of canine (from contact point) on both sides (8) Determination of anterior crowding was performed by Little criterion [ 19 ] and by measuring the total overflow resulting from crowding in the distance from canine to canine. The resulting number was placed in each of these groups: no crowding, 0 mm; light crowding, 1 to 3 mm; medium crowding, 4 to 6 mm; severe crowding, 7 to 9 mm; and very severe crowding, 10 mm …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After molding the relevant jaw and preparing the cast, the following items were examined: (7) Determining the distal movement of the canine tooth independent of other anterior teeth towards the space obtained from the extraction of the first deciduous molars by comparing the distance between the mesial surface of lateral teeth to the distal surface of canine (from contact point) on both sides (8) Determination of anterior crowding was performed by Little criterion [ 19 ] and by measuring the total overflow resulting from crowding in the distance from canine to canine. The resulting number was placed in each of these groups: no crowding, 0 mm; light crowding, 1 to 3 mm; medium crowding, 4 to 6 mm; severe crowding, 7 to 9 mm; and very severe crowding, 10 mm …”
Section: Methodsmentioning
confidence: 99%
“…(8) Determination of anterior crowding was performed by Little criterion [ 19 ] and by measuring the total overflow resulting from crowding in the distance from canine to canine. The resulting number was placed in each of these groups: no crowding, 0 mm; light crowding, 1 to 3 mm; medium crowding, 4 to 6 mm; severe crowding, 7 to 9 mm; and very severe crowding, 10 mm…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, the bonding procedure of lingual retainers, in individuals treated with or without extraction was evaluated. According to Little's Irregularity Index, it was reported that crowding up to 3 mm: expansion, crowding between 3 and 5 mm: interproximal enamel reduction, and crowding above 5 mm: treatment with extraction may prevent the relaps [17]. However, the treatments with non-extraction or extraction of first premolars showed a similar tendency to incisor relapse [18].…”
Section: Discussionmentioning
confidence: 99%
“…Space maintainers can be utilized for this purpose. Early primary molar loss might result in a reduction in arch length, increasing the severity of crowding/malocclusion; therefore, in the affected patient, every effort should be made to preserve the natural leeway space [29]. The unilateral loss of a primary canine or first molar can result in a significant centerline disparity and mesial migration of the buccal segments, which is another critical clinical condition to preserve space [38].…”
Section: Prophylaxismentioning
confidence: 99%